Organic Waste Management in Markets Based on Waste Characteristics: A Case Study of Markasan Market in Nanga Pinoh, Melawi - Evinsyah Putra Nasution; Evi Gusmayanti; Aji Ali Akbar (Sean Institute, 2025)
Traditional markets are key centers of economic activity and major sources of organic waste generation in Indonesia. This study aims to analyze the volume, density, and composition of organic waste at Markasan Market, Nanga Pinoh, and to identify traders’ participation in waste management. The research employed a quantitative approach through direct measurement and surveys involving 58 traders representing four main commodities: vegetables, fish, poultry, and fruits. Data were collected using observation, interviews, and questionnaires, then analyzed descriptively. The results show that waste generation is dominated by organic waste (>80%) with an average density of 104.68 kg/m³ and a generation rate of 2.74 kg/unit/day. The largest composition comes from poultry feathers, while the smallest is vegetable residue. Traders’ knowledge, facilities, and compliance with waste management are categorized as moderate. The main issues include limited waste facilities, low awareness among traders, and weak regulatory enforcement. The study recommends improving waste storage facilities, formulating stricter regulations, conducting continuous training and awareness programs, and implementing incentive and penalty systems. Additionally, utilizing organic waste for compost, animal feed, or biogas is considered a promising strategy to support 3R (reduce, reuse, recycle) principles and Sustainable Development Goal 12 (Responsible Consumption and Production). This research contributes to developing effective, healthy, and sustainable waste management models for traditional markets and provides a practical reference for local governments and market managers.